Improving the in vitro penetration of niacinamide using span 60-based niosomal system in gel formulation - Rise Desnita; Sri Luliana; Zainab Kasim (Universitas Ahmad Dahlan, 2018)
Niacinamide is one of the components of cosmeceutical products that reported to have skin benefits for the treatment of skin pigmentation, acne and wrinkles. However, the dermal penetration of niacinamide is poor. The carrier system which can be selected to carry the compound through the stratum corneum layer is the niosome system using span 60. This study was aimed to determine the concentration of span 60 that can trap niacinamide optimally and the ability of niosome system span 60 to increase in vitro penetration of niacinamide in gel formulation. The different formulations of nicotinamide niosome were formulated with variance concentrations of Span 60, that is, formula A 100 μmol, formula B 150 μmol, and formula C 200 μmol. The entrapment efficiency testing was conducted using dialysis membrane. The gel formulation was prepared in two formulas, niacinamide niosome gel and niacinamide gel (without niosomes) and tested diffusion using Franz diffusion cell flow-through type. The result show that Formula A provides the most optimum entrapment efficiency of 99.03±0.026%. The results of the in vitro skin penetration studies for 8 hours indicate that the niosomal formulation using Span 60 could increase skin penetration with the percent cumulative amount of niacinamide niosomes was 82.87±1.6932% compared to niacinamide in gel without noisome system about 70.27±5,3212%.